Gastroenteritis at the Pediatric Ward of Tembakau Deli Hospital, Medan, in 1988 - Faisal Ramyuzal Nasution; Gabriel Panggabean; M. Sjabaroeddin; Zakaria Siregar (Indonesian Pediatric Society, 1991)
In a period of 1 year (1 January - 31 December 1988) a retrospective study on patients admitted to the Pediatric ward of Tembakau Deli Hospital, Medan, was done.This hospital is a referral hospital for patients from hospitals of Dept. of Plantation in North Sumatera and Aceh.During year 1988, there were 1339 infants and children hospitalized at the Pediatric ward Tembakau Deli, Medan. Of these patients, 183 had gastroenteritis; it was most frequently found in the age group of 0-13 months (46.4%). The patients consisted of 53.55% males and 46.45% females.Most of the patients i.e. 140 (76.51%), had good nutrition. Malnutrition were found in 31 patients where 16.94% among them were moderate malnutrition, and 12 patients (6.55%) had malnutrition.The total mortality rate of gastroenteritis in this study was 2.18% which was usually associated with severe complications while pure gastroenteritis showed no (0%) mortality.